Platelet Factor XIII Increases the Fibrinolytic Resistance of Platelet-Rich Clots by Accelerating the Crosslinking of α2-Antiplasmin to Fibrin - Reed, Guy L; Matsueda, Gary R; Haber, Edgar (Thrombosis and Haemostasis, 1992)
Platelet clots resist fibrinolysis by plasminogen activators. We hypothesized that platelet factor XIII may enhance the fibrinolytic resistance of platelet-rich clots by catalyzing the crosslinking of α2-antiplasmin (α2AP) to fibrin. Analysis of plasma clot structure by polyacrylamide gel electrophoresis and immunoblotting revealed accelerated α2AP-fibrin crosslinking in platelet-rich compared with platelet-depleted plasma clots. A similar study of clots formed with purified fibrinogen (depleted of factor XIII activity), isolated platelets, and specific factor XIII inhibitors indicated that this accelerated crosslinking was due to the catalytic activity of platelet factor XIII. Moreover, when washed platelets were aggregated by thrombin, there was evidence of platelet factor XIII-mediated crosslinking between platelet α2AP and platelet fibrin(ogen). Specific inhibition (by a monoclonal antibody) of the α2AP associated with washed platelet aggregates accelerated the fibrinolysis of the platelet aggregate. Thus in platelet-rich plasma clots, and in thrombin-induced platelet aggregates, platelet factor XIII actively formed α2AP-fibrin crosslinks, which appeared to enhance the resistance of platelet-rich clots to fibrinolysis.